2006
DOI: 10.1177/0091270006292625
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of In Vivo P‐glycoprotein and Cytochrome P450 3A Activities

Abstract: Digoxin and midazolam are routinely used as probe drugs to measure in vivo activity of P-glycoprotein (P-gp) and cytochrome P450 3A4/5 (CYP3A), respectively. We investigated whether digoxin and midazolam could be coadministered to simultaneously determine P-gp and CYP3A activity without a significant pharmacokinetic interaction. In a randomized crossover design, digoxin (0.5 mg oral) or midazolam (2.0 mg oral) was administered individually or in combination (digoxin 1 hour after midazolam) to 14 healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 44 publications
(83 reference statements)
4
34
0
Order By: Relevance
“…Using historical data for MDZ in healthy volunteers (Wang et al, 2001;Kirby et al, 2006), we conducted an a priori power analysis using the AUC of MDZ as the primary outcome measure. Assuming equal variance between control and treatment groups, our analysis indicated that n ϭ 7 would provide 80% power (␣ Ͻ 0.05) to discern 54 and 41% changes in oral and intravenous MDZ AUC, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Using historical data for MDZ in healthy volunteers (Wang et al, 2001;Kirby et al, 2006), we conducted an a priori power analysis using the AUC of MDZ as the primary outcome measure. Assuming equal variance between control and treatment groups, our analysis indicated that n ϭ 7 would provide 80% power (␣ Ͻ 0.05) to discern 54 and 41% changes in oral and intravenous MDZ AUC, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were dried down and reconstituted in acetonitrile/water (9/1), and the concentration of 19-hydoxymidazolam was determined by liquid chromatography-mass spectrometry [Waters Alliance 2695 HPLC (Waters, Milford, MA) interfaced with Waters Micromass Quattro Micro] using an electrospray ion source. The mobile phase consisted of 0.1% (v/v) acetic acid in water and 0.1% (v/v) acetic acid in acetonitrile, as described previously (Kirby et al, 2006). The separation was performed with a Zorbax Eclipse SB-C18 column (2.1 Â 150 mm, 5 mm; Agilent Technologies, Santa Clara, CA) at a flow rate of 0.25 ml min…”
Section: Cyp3a Activity Measurementmentioning
confidence: 99%
“…A calibration curve ranging from 2.5 to 250 ng/ml of 1Ј-OH-MDZ was prepared in blank cell media. The samples were subjected to liquid-liquid extraction and the amount of 1Ј-OH-MDZ was measured by liquid chromatography-mass spectrometry as described previously (Kirby et al, 2006b) with the following minor modifications. To a 0.5-ml aliquot of cell lysate, a stable labeled internal standard (d 5 -1Ј-OH-midazolam, m/z 346.9, 25 ng) was added.…”
mentioning
confidence: 99%